Ocena jakości życia pacjentów chorych na reumatoidalne zapalenie stawów w okresie pandemii SARS-CoV-2 - Jędrasik, Karolina; Gaweł, Zofia; Pietruszka, Martyna; Jankowska-Polańska, Beata; Krysiak, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The aim of the study is to present how the SARS-CoV-2 pandemic influenced the quality of life (QOL) of patients with rheumatoid arthritis. Additionally, an evaluation of the satisfaction and importance of teleconsultations with a primary healthcare physician was performed to investigate the impact of this type of contact on the quality of life of patients with descibed disease. The study was conducted among 146 patients with rheumatoid arthritis, with the help of quality of life questionaire and self-authored form, as well as medical data. The quality of life during the pandemic occured to be low in the cases of almost half of the respondents (circa 49,3%). The results of the research proved that the quality of life depended on the severity of the symptoms associated with the underlying disease. The following factors had a negative impact on the QoL assessment: lack of activity in family and work life, and a small amount of pastimes related to relaxation and enjoyment. Patients complain about the lack of participation in important events and the inability to be active in everyday activities as well as home and professional activities, which was significantly related to the QoL level. More than half of the respondents took part in teleconsultations during the pandemic. The results of the research show that for the vast majority of respondents contact with a doctor during the pandemic was satisfactory, however, access to health care was difficult. According to the obtained informaton, it was found out, that the quality of life of rheumatoid arthritis patients during the SARS-CoV-2 pandemic is low; Moreover, the assessment of the quality of life is negatively affected by the severity of the disease symptoms and the lack of activity in everyday activities as well as social and professional activity; furthermore, patients with rheumatoid arthritis, whenever possible, participate in teleconsultations, and its quality is satisfaing; unfortunately, patients draw attention to difficult contact with the doctor, what requires expansion of availability of these visits.
Keywords: rheumatoid arthritis; quality of life; COVID-19 pandemic; teleconsultation